The Image of The Other in Jewish Interpretations of Alenu - Hoffman, Jeffrey (Studies in Christian-Jewish Relations, 2015)
The image of the non-Jewish Other stands at the center of the ancient Jewish prayer, Alenu. In it, the Other is contrasted with the Jews as the only worshipers of the true God. Alenu juxtaposes the correctness of Israel’s religion with the erroneousness of the Other’s religion. Jewish interpretations of Alenu, over time and across various geographical locations, form an interesting bellwether of Jewish approaches to the Other in general. The earliest versions of the prayer – in the Hekhalot Literature and in the Rosh ha-shanah liturgy – did not shy away from the severe image of the Other. The medieval commentators too continued the trend of acknowledging the anti-Other content of Alenu in a straightforward way and several medieval versions even amplified the negative image. Beginning with the early modern period however, and the commencement of even partial acceptance of Jews into non-Jewish society, all of the commentaries attempted to diminish that negative image to one degree or another. Contemporary Jewish commentaries produced for popular audiences (and some produced for academic audiences) softened the image of the Other in their interpretations of Alenu and all of the prayer books produced for contemporary American Jews that were surveyed similarly played down the negative depiction of the Other in this prayer. All of these trends in the way Jewish interpreters viewed the non-Jewish Other reflected the Jewish perception of non-Jews in the various periods.